Pembuatan Bodi Prototype Mobil Hemat Energi Berbahan Fiberglass di Politeknik Negeri Jember - Putra, Dwiki Indriansyah; Rahmat, Saiful; Firmansyah, Indra; Affandi, Achmad (Jurnal Teknik Terapan, 2023)
The use of fiberglass in Indonesia is still limited for manufacturing. That only vehicle body components for mini buses and buses, there are still not many domestically assembled custom car vehicles that include their original specifications as bodies made of fiberglass. This study aims to: Determine the right type of body material to be used in Energy Saving cars” Jember State Polytechnic, Knowing the design of the KMHE Polije car body with fiberglass as the main material. This study used the Research and Development (R & D) method with the research object taken was the design of the KMHE Polije car. Data collection methods were carried out in making the body, namely the literature method, the observation method and the interview method. After determining the desired method, then the manufacture of the car body is carried out. In its manufacture, several preparations are required, namely making designs, making molds, and making bodies using fiberglass media. Making the body adjusted to the dimensions of the length. The conclusion of this research is that the body of the Energy Saving Car prototype can be attached to the frame properly after the car is used or driven and the Energy Saving Car prototype body made of fiberglass material is very appropriate because it has a light character, easy to shape. This research was conducted from the feasibility stage with design validation to making the product and testing it. Based on the validation results by design experts, an average score of 85% is obtained with the "Valid" criteria so that the product is feasible to use.